2016
DOI: 10.4269/ajtmh.16-0116
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis Outbreak in Children and Adults in Two Areas in Israel

Abstract: Abstract. Two parallel outbreaks of Brucella melitensis infection occurred in 2014 in two geographical areas in Israel. In two medical centers in northern Israel and one medical center in Jerusalem, 102 patients (58 children, 47 adults) were diagnosed with brucellosis. Most patients (N = 76, 72%) were Muslim Arabs, 28 (27%) were Druze, and one was Jewish. The source of infection was often traced to cheese from the Palestinian Authority. Biovar-1 was evident in 98% in northern Israel but only in 42% in Jerusale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Some scholars reported that enlarged lymph nodes, spleen and liver, skin rashes, pharyngitis [ 89 ], and hematological and respiratory complications were more frequently observed in children than in adults [ 90 ]. Children had higher rates of hepatitis, osteoarticular manifestations [ 91 ], and lower rates of meningitis, endocarditis, spondylitis, and the progression to chronicity [ 92 ]. In the study, we found clinical differences between children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars reported that enlarged lymph nodes, spleen and liver, skin rashes, pharyngitis [ 89 ], and hematological and respiratory complications were more frequently observed in children than in adults [ 90 ]. Children had higher rates of hepatitis, osteoarticular manifestations [ 91 ], and lower rates of meningitis, endocarditis, spondylitis, and the progression to chronicity [ 92 ]. In the study, we found clinical differences between children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…As in other investigations, the most common manifestation was fever, followed by osteoarticular symptoms, which were more pronounced in the pediatric group (required a longer hospitalization). No head or neck manifestations were reported in this study …”
Section: Discussionmentioning
confidence: 65%
“…No head or neck manifestations were reported in this study. 20 Searching all English-language papers for additional brucellosis cases involving predominantly the otolaryngology/head and neck region revealed one case of Brucellainduced suppurative parotitis and a case of neurobrucellosis complicated by vestibulocochlear nerve palsy. 21…”
Section: Discussionmentioning
confidence: 99%
“…Long-term combined antibiotic therapy prevents relapses. The combined treatment of doxycycline-rifampicin or doxycycline-streptomycin for six to eight weeks is the first choice in epididymoorchitis (2,19). Surgical drainage and rarely orchiectomy may be required in patients with testicular abscess (20).…”
Section: Discussionmentioning
confidence: 99%